MODEL PEMBELAJARAN COOPERATIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PKN MATERI NEGARA KESATUAN REPUBLIK INDONESIA MELALUI METODE ROLE PLAYING PADA SISWA KELAS V SDN TEGAL BESAR 04 KECAMATAN KALIWATES TAHUN PELAJARAN 2016/2017: SDN TEGAL BESAR 04 KECAMATAN KALIWATES - TINJUNG TINJUNG (Mitra Pendidikan, 2021)
This research was conducted based on the findings of the class, to improve the learning outcomes of Citizenship Lessons (PKn) after the role-playing learning method was applied through the role-playing method (Role Playing) with the cooperative learning model of learning in fifth grade students of SDN Tegal Besar 04 Kaliwates District Academic Year 2016/ 2017. This study uses a quantitative approach obtained from the results of formative test scores. From these results can be used to measure the level of success of learning. From the results of the formative test scores, it can be seen the success rate of using the role playing method in increasing student motivation. The quantitative data is made in accordance with the assessment guidelines that have been made by the teacher. After the teacher gives an assessment and then analyzes the questions. The benefits of this research are expected to increase thinking creativity, motivation and student learning outcomes, and teachers at SDN Tegal Besar 04 Kaliwates District are expected to be used as development materials to improve the teaching and learning process in order to improve the quality of education.